PENILAIAN TEKNIS DAN EKONOMIS KUALITAS PENGELOLAAN LINGKUNGAN STOCKPILE BATUBARA UNTUK LINGKUNGAN BERKELANJUTAN - Juniah, Restu; Ambarita, Novitasari; Syarifudin; Zakir, Syaifudin; Rahmi, Hisni; Amanda, Ridho Rizky (Indonesian Mining Journal, 2025)
Coal mining has positive impacts in the form of increasing the national economy and people's income. However, it also has negative impacts, including the decrease of environmental quality such as air, soil, and noise, as well as the potential for spontaneous combustion. The research was conducted to assess the technical and economic aspects of environmental management at coal stockpiles in the Tarahan Port Unit of PT Bukit Asam Tbk to support environmental sustainability. The technical assessment of stockpile environmental management was carried out by comparing observation results with the Environmental Management and Monitoring Plan Document (RKL/RPL) and Indonesia’s applicable Environmental Quality Standards. The economic assessment focused on the cost of environmental monitoring and management by observing the discrepancies between the planned and realization in the first and second quarters. The technical assessment results show that environmental management at the stockpile has been implemented effectively. Air quality parameters and noise levels remain below the established standards, soil quality is classified good as indicated by vegetation growth, and no spontaneous combustion occurred during the observation period. The economic assessment revealed a discrepancy of 2.02% between the planned cost of IDR 121,183,548 to the actual realization of IDR 123,641,668. This increase was attributed to the construction of a dust reduction system and an operational chimney for the 2X8 MW Steam Power Plant, through the use of Electrostatic Precipitators. The study recommends a detailed inventory of environmental cost plans and potential cost escalation to anticipate risk factors. It also highlights the need for regular maintenance of machines that are known to frequently produce emissions. These efforts are expected to reduce the emissions and lower the costs of environmental management and monitoring.